Improving drug delivery strategies for lymphatic filariasis elimination in urban areas in Ghana. - Nana-Kwadwo Biritwum; Bertha Garshong; Bright Alomatu; Dziedzom K de Souza; Margaret Gyapong; Dominique Kyelem (PLoS Neglected Tropical Diseases)
The Global Program to Eliminate Lymphatic Filariasis (GPELF) advocates for the treatment of entire endemic communities, in order to achieve its elimination targets. LF is predominantly a rural disease, and achieving the required treatment coverage in these areas is much easier compared to urban areas that are more complex. In Ghana, parts of the Greater Accra Region with Accra as the capital city are also endemic for LF. Mass Drug Administration (MDA) in Accra started in 2006. However, after four years of treatment, the coverage has always been far below the 65% epidemiologic coverage for interrupting transmission. As such, there was a need to identify the reasons for poor treatment coverage and design specific strategies to improve the delivery of MDA. This study therefore set out to identify the opportunities and barriers for implementing MDA in urban settings, and to develop appropriate strategies for MDA in these settings. An experimental, exploratory study was undertaken in three districts in the Greater Accra region. The study identified various types of non-rural settings, the social structures, stakeholders and resources that could be employed for MDA. Qualitative assessment such as in-depth interviews (IDIs) and focus group discussions (FGDs) with community leaders, community members, health providers, NGOs and other stakeholders in the community was undertaken. The study was carried out in three phases: pre-intervention, intervention and post-intervention phases, to assess the profile of the urban areas and identify reasons for poor treatment coverage using both qualitative and quantitative research methods. The outcomes from the study revealed that, knowledge, attitudes and practices of community members to MDA improved slightly from the pre-intervention phase to the post-intervention phase, in the districts where the interventions were readily implemented by health workers. Many factors such as adequate leadership, funding, planning and community involvement, were identified as being important in improving implementation and coverage of MDA in the study districts. Implementing MDA in urban areas therefore needs to be given significant consideration and planning, if the required coverage rates are to be achieved. This paper, presents the recommendations and strategies for undertaking MDA in urban areas.